An integrative model for understanding and managing ethical behavior in business organizations - Stead, W. Edward (Journal of business ethics, 1990)
Managing ethical behavior is a one of the most pervasive and complex problems facing business organizations today. Employees' decisions to behave ethically or unethically are influenced by a myriad of individual and situational factors. Background, personality, decision history, managerial philosophy, and reinforcement are but a few of the factors which have been identified by researchers as determinants of employees' behavior when faced with ethical dilemmas. The literature related to ethical behavior is reviewed in this article, and a model for understanding ethical behavior in business organizations is proposed. It is concluded that managing ethics in business organizations requires that managers engage in a concentrated effort which involves espousing ethics, behaving ethically, developing screening mechanisms, providing ethical training, creating ethics units and reinforcing ethical behavior.